2019
DOI: 10.3390/polym11091495
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Weathering of Polylactide-Based Composites Filled with Linseed Cake: The Influence of Time and Oil Content within the Filler

Abstract: This paper presents the effects of accelerated weathering on the properties of polylactide (PLA) composites filled with linseed cake. The particle-shaped waste filler with different linseed oil content (0.9–39.8 wt %) was incorporated with constant amount of 10 wt % to a polymeric matrix and subjected to accelerated weathering tests with different exposition times. The structure of the composites, their mechanical, thermal, and thermo-mechanical properties were evaluated by means of scanning electron microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 60 publications
4
40
0
Order By: Relevance
“…The presence of the oil in the F3 formulation would avoid the mentioned effect it gives the fiber a more hydrophobic character. During the first stage of the hydrolytic degradation process, the samples containing oil as plasticizer are resistant to hydrolytic degradation, as degradation progresses, the plasticizer migrates, and the hydrolytic media can diffuse inside the fibers [107]. Therefore, the hydrolytic degradation of fibers added with oils is more noticeable for longer times as evidenced in the morphological changes of the fibers.…”
Section: Fiber Hydrolytic Degradationmentioning
confidence: 99%
“…The presence of the oil in the F3 formulation would avoid the mentioned effect it gives the fiber a more hydrophobic character. During the first stage of the hydrolytic degradation process, the samples containing oil as plasticizer are resistant to hydrolytic degradation, as degradation progresses, the plasticizer migrates, and the hydrolytic media can diffuse inside the fibers [107]. Therefore, the hydrolytic degradation of fibers added with oils is more noticeable for longer times as evidenced in the morphological changes of the fibers.…”
Section: Fiber Hydrolytic Degradationmentioning
confidence: 99%
“…Polymer hybrid materials contain fillers or modifiers that have different functionalities, thanks to which they are characterized by unique usable, technological, and processing properties. Designing a composite material requires taking the processing technique, the susceptibility of all components to heat, mechanical treatment, durability, and the ability to create compounds into account [1][2][3][4][5]. Epoxy resins can be in the form of liquids, pastes, or powders, which significantly facilitates their modification by mixing with reactive or non-reactive additives [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…This outcome is surprising, as the oil-rich samples presented higher thermal degradation temperatures. It may be suggested that the composites characterized by different morphology and crystallinity (as described in our previous article) [23] also present different thermal conductivity and specific heat, therefore, the needed energy is absorbed by the sample at different temperature. LC, a multicomponent filler, which comprises of cellulose, mucilage, proteins, and oil as well as mineral compounds, [51,52] which need different activation energy to decompose, as it is reflected by the shape of the E a vs α curve.…”
Section: Samplementioning
confidence: 92%
“…As a result, five grades of the filler characterized with the oil content of 0.9% to 39.8% were obtained: LC-0.9, LC-4.6, LC-17.7, LC-30.4, and LC-39.8, where the number is the oil content in weight percent, determined by a Büchi Universal Extraction System B811 using petroleum ether as a solvent, with extraction time of 150 minutes at a temperature of 100 C. A more detailed description of the filler preparation can be found in our previous article. [23]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation